Ruminal volatile fatty acid concentration and methane gas production in sheep (Ovis aries) fed two types of basal diets with of without Gliricidia sepium legume forage supplementation - Gaspe, R-Jun Frederick A.; Bestil, Lolito C.; Obitsu, Taketo (Annals of Tropical Research, 2023)
The aim of this study was to clarify whether the type of forage diets, Napier grass (Pennisetum purpureum) vs. urea-treated rice straw, and supplementation with Gliricidia sepium affect rumen VFA production and methane emission as well as intake and digestibility in ruminants. The experiment was set up in a randomized complete block design (RCBD) composed of four treatments namely: Napier grass (T1), Napier + legume forage (T2), urea-treated rice straw (T3), and urea-treated rice straw + legume forage (T4). Each treatment was divided into four blocks (n=16) based on body weight and sex combination. The daily dry matter intake tended to increase from treatments supplemented with G. sepium (T2 and T4) compared to treatment-fed pure basal diet alone (T1 and T3). Intake relative to metabolic weight (BW 0.75) is high in T2 and T4. The molar concentration of volatile fatty acid was higher in T1, which was found comparable with T2 and T3, while T4 has the lowest. The molar proportion of acetate tended to increase in T1 and T3, while the propionate concentration was significantly high in T2 and T4 leading to lesser CH4/CO2 production respectively. These results confirmed the potential of G. sepium as a methane-mitigating supplement to basal diets such as Napier and urea-treated rice straw as feed to ruminants.